STRATEGI PEMBELAJARAN EKSTRAKURIKULER PADUAN SUARA DI SMP NEGERI 2 JEPARA - Strinariswari, Ratna Luhung; Susetyo, Bagus; Raharjo, Eko (Jurnal Seni Musik, 2015)
Extracurricular choir aims to develop the talent of singing of the students, develop creative power, motivation, student attitudes that can lead to good interest.The problem studied in this research is how learning strategies extracurricular choir in SMP Negeri 2 Jepara? The purpose of this study was to determine and describe the learning strategy extracurricular choir in SMP Negeri 2 Jepara. This study used a qualitative descriptive approach. Data analysis using techniques: observation, interviews, and documentation. The data collected is then described, reduced (simplified), are presented and summarized in the form of words. The results showed that in 1991 became the origin of extracurricular choir in SMP Negeri 2 Jepara. Learning extracurricular choir with selecting participants include planning, preparing teaching materials, preparing the strategies that will be used, making the training schedule, and implement learning esktrakurikuler chorus along with the use of strategies and methods are good, true and correct. To enhance these activities, the needed infrastructure, preliminary activities, the submission of information, participation of learners, materials, training, and evaluation. Extracurricular choir in SMP Negeri 2 Jepara using expository teaching strategies, cooperative learning strategies and affective learning strategies. In practice, teacher deliver material with lectures, forming groups 3-4 and do the exercises in accordance with the material being taught vocal technique and practice, after it presented alternately in front of the other group.